Sword art online. Progressive, 006 - Kawahara, Reki (Yen Press, 2018)
The war between elves rages on, with Kirito and Asuna caught in the middle The forest elves seek the dark elves' Secret Key, but to what end? Though Kirito tries to stay detached, Asuna can't help being swept along for the ride. Kizmel is supposed to be just an NPC, right? But then why does she seem so very human...?